Facile assembly of 2D α-zirconium phosphate supported silver nanoparticles: superior and recyclable catalysis. (2nd June 2020) - Xu, Yonghang; Zhou, Fangya; Chen, Min; Hu, Huawen; Lin, Limiao; Wu, Jingshu; Zhang, Min
Abstract : A novel, efficient and durable two-dimensional ZrP@PDA/Ag nanocatalyst for the reduction of 4-nitrophenol. Abstract : A novel, efficient and durable ZrP@PDA/Ag nanocatalyst was prepared via the facile reduction and deposition of silver nanoparticles (AgNPs) on two dimensional (2D) α-zirconium phosphate (ZrP) nanosheets using bio-inspired dopamine chemistry. The formation, adhesion and dispersion of AgNPs were confirmed by the full morphological and structural characterizations including SEM, TEM, FTIR, TGA, WXRD, and XPS. This ZrP@PDA/Ag nanocatalyst was evaluated by the reduction of 4-nitrophenol into 4-aminophenol, utilizing UV-vis absorption spectroscopy to monitor the reaction solution with a trace silver content of 0.125 μg mL −1 . ZrP@PDA/Ag exhibits a superior catalytic activity compared with other noble metal nanocatalysts due to its high turnover frequency of 32.36 min −1 at room temperature without stirring, which is as high as almost 10 times that of the reported nanocatalysts using 2D graphene and silica supports. Furthermore, due to the excellent catalytic recyclability of ZrP@PDA/Ag it has very promising prospects in the treatment of organic pollutants in water.